(untitled) (Metallurgy and Foundry Engineering, 2011)
The properties of alloys used for centrifugally cast catalytic tubes depend on the stability of carbides hardening the alloy at an operating temperature. Tubes cast in centrifugal process are characterised by structure changing on the cross-section: the outer layer is composed of columnar crystals, while inner layer has the structure of equiaxed crystals. The properties of these two zones differ and have a major influence on the casting behaviour during operation. The aim of this study was to determine the volume fraction of Cr and Nb carbides in the zone of columnar and equiaxed crystals under different inoculation regimes. It was found that the type of the used microadditives changes the amount of carbides in the investigated zones of castings.